THE EFFECT OF LEARNING VIDEO USE ON SEWING SKILLS WITH KASAB THREAD IN THE FASHION DESIGN COURSE FOR SEMESTER IV STUDENTS OF THE PERFORMING ARTS EDUCATION STUDY PROGRAM - Sarah Nadia; Umul Aiman (STMIK Indonesia Banda Aceh, 2026)
This study aims to determine the effect of the use of instructional videos on the ability to sew kasab thread in the Fashion Design course of Semester IV students of the Performing Arts Education Study Program. The background of this study focuses on the need for innovation in learning media in the era of globalization, where lecturers are expected not only to deliver material, but also to function as innovators in the field of education. Instructional videos are considered an appropriate solution because they can present visualizations of sewing steps that are clear, structured, and can be repeated according to student needs. The approach applied in this study was a quasi-experimental with quantitative methods, involving two classes with 24 students each. The experimental group used a learning video, while the control group used a traditional learning module. Data were collected through practical tests of sewing kasab thread with assessments on aspects such as technical accuracy, neatness of results, creativity, timeliness, density, and stitch strength. Data analysis was performed using t-tests and ANOVA with the help of SPSS version 21 software. The results of the study showed a significant difference in kasab thread sewing skills between students who received instruction with learning videos and without learning videos. The recorded significance value of 0.000 < 0.05 indicates that the null hypothesis must be rejected, which means that the use of learning videos has a real impact on improving kasab thread sewing skills. These findings prove that video-based learning media is very effective in improving students' practical skills and also contributes to the preservation of Acehnese culture through traditional clothing creations.